2019
DOI: 10.1029/2018ja026152
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐Scale Traveling Ionospheric Disturbances Induced by Typhoon Chan‐hom Over China

Abstract: This paper reports the ionospheric response to Typhoon Chan-hom using Global Positioning System network data from China, combined with observations of an ionosonde chain. Two medium-scale traveling ionospheric disturbances (MSTIDs) were observed around the two landing times of Typhoon Chan-hom. The MSTID with a phase fronts aligned in the north-south direction was detected on the east coast of China at 16:50-18:40 UT on 11 July 2015 and moved westward with a mean horizontal phase velocity of 268 m/s and period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The time period T is calculated using the Lomb‐Scargle periodagram of TEC perturbations of individual stations and averaging at the end. Finally, the horizontal wavelength ( λ h ) is estimated from the relation, λ h = T × V ph (Song et al, 2017, 2019). The time period and horizontal velocity deduced for 8 and 9 April are ~23 min, ~225 m/s and ~23 min, ~230 m/s, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time period T is calculated using the Lomb‐Scargle periodagram of TEC perturbations of individual stations and averaging at the end. Finally, the horizontal wavelength ( λ h ) is estimated from the relation, λ h = T × V ph (Song et al, 2017, 2019). The time period and horizontal velocity deduced for 8 and 9 April are ~23 min, ~225 m/s and ~23 min, ~230 m/s, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nishioka et al (2013) have given a clear observational evidence of concentric waves developed in the ionosphere after the 2013 Moore EF5 tornado. Using the dense GPS network data from China, Song et al (2019) reported the observation of two MSTID events during the Typhoon Chan‐hom. Even though there are several studies that reported the development of MSTIDs and TIDs due to TCs, studies on the EPB/ESF irregularities associated with TCs are very few (Ke et al, 2019; Lou et al, 2019; Yang & Liu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, denser Global Positioning System (GPS) observations provide important data for the study of ionospheric variations, allowing the continuous monitoring of large-scale ionospheric disturbances caused by typhoons [11][12][13][14] and earthquakes [15][16][17]. The characteristics of traveling ionospheric disturbances (TIDs) are consistent with the theory of gravity waves.…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, more analysis and studies are needed. Furthermore, the disturbance propagation direction, period, and speed do not clearly follow the typhoon [11].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation